Development of mycoinsecticide formulations with Beauveria bassiana and Metarhizium brunneum for the control of Orosanga japonica (Hemiptera: Ricaniidae). (28th April 2021) - Biryol, Seda; Güney, Ebru; Eski, Ardahan; Bayramoğlu, Zeynep; Sezen, Kazım; Demirbag, Zihni; Demir, İsmail
Abstract: Entomopathogenic fungi are promising microbial agents for agricultural pests, especially piercing‐sucking insects. In this study, eight indigenous fungal isolates including four isolates of Metarhizium brunneum and four isolates of Beauveria bassiana were tested on Orosanga japonica Melichar (Hemiptera: Ricaniidae) in order to find an effective control agent that can be utilised for the development of oil‐based fungal mycoinsecticides. In the screening test using 1 × 10 7 spores ml −1 concentration, KTU‐24 ( B . bassiana ) and KTU‐51 ( M . brunneum ) had the highest lethal activity against nymphs and adults of the target pest. Also, at the highest concentration (10 9 spores ml −1 ), KTU‐24 showed 92.33 and 94.88% mortality on nymphs and adults at the dose–response tests, respectively, and the KTU‐51 isolate showed 100% mortality on both stages of O . japonica under laboratory conditions. With these results, KTU‐24 and KTU‐51 isolates were used to develop biopesticides. While the mass production of B . bassiana was carried out with liquid‐state fermentation, solid‐state fermentation was used for mass production of M . brunneum . Spores of both isolates were formulated in oil, and products were named as RICANICIDAL Bbas ‐TR61 and RICANICIDAL Met ‐TR61, respectively. Formulations caused over 97% mortality against nymphs and adults of O . japonica under field conditions and both formulations showed higher efficacy than commercial mycoinsecticides at 10 8 spores/ml concentration 20 days after treatment. The currents study shows that both mycoinsecticide formulations are highly promising for management of O . japonica . Abstract : In this study, eight indigenous fungal isolates including Metarhizium brunneum and Beauveria bassiana were tested on Orosanga japonica Melichar (Hemiptera: Ricaniidae) in order to find an effective control agent that can be utilised for the development of oil‐based fungal mycoinsecticides.